Analysis of Column and Beam Minimum Reinforcement Requirements on the Building Structure of the Faculty of Psychology, University of Semarang - Widorini, Trias; Crista, Ngudi Hari; Anggraini, Lila (Science and Technology Research Centre, Universitas PGRI Semarang, 2021)
In formulating the seismic design criteria for a building at ground level or determining the amplification of the peak earthquake acceleration from the bedrock to the ground for a site, the site must be classified first. Site class assignment must be carried out through field and laboratory soil investigations. Site Class consists of SA (hard rock), SB (rock), SC (medium soil), SE (soft soil) and SF (special soil). SNI 1726: 2019 with various classes of SB, SC, SD and SE sites. From the analysis results, it is found that the variation of soil site classes has an effect on the area of minimum reinforcement requirements, except for the logitudinal reinforcement requirements of the lower support beam for site class variations, the value is fixed. The variation of soil site classes has a significant effect on the area requirements of the longitudinal reinforcement in the column. The largest requirement for column longitudinal reinforcement is Soft Soil Site Class (E) and the smallest requirement is Rock Site Class (B).